Pengembangan Media Digital Games Based Learning (DGBL) pada Materi Operasi Himpunan Matematika Kelas VII di SMP Negeri 9 Semarang - Cahyo, Niko Dwi; Sunardiyo, Said (Edu Komputika Journal, 2016)
Generally, this research aims to design, create and analyze quality and it performance as a media for Digital Games Based Learning method on mathematical set operations in Junior High School. Development refers to this research designs is Research and Development (R & D) using models DGBL-ID (Digital Games Based Learning-Instructional Design) with such stages of analysis, design, development, quality testing and implementation. The calibration results from the aspect of functionality indicates that all the major functions and media interface is run as expected. In the aspect of performance showing media DGBL can run efficiently with the consumption of CPU and memory respectively by 1.5% and 55.7 Mb. Usability eligibility percentage is at 87.5%. The assessment of the feasibility of the media by media specialists and subject matter experts show that media DGBL is in the category of valid. The results of the implementation of DGBL media in the learning process to the 30 students of grade VII from 9th State Junior High School in Semarang, showed 76.7% of students give a high responded and passion for media DGBL. Based on the results of research and discussion, we can conclude that the media DGBL is feasible in learning mathematical set operations in 9th State Junior High School in Semarang.